Negação da laicidade, conservadorismo e Pedagogia Histórico-Crítica na escola pública brasileira - Ferreira, Vanessa Scherer (2021)
This research addresses the religious interference in Brazilian public education after the implementation of the Secular State in 1890 to the present day, starting from the roots of religious fundamentalism in the country and from the very conceptualization of secularism, through documentary and bibliographical research. It seeks to analyze and understand the power relations that historically influence formal education, as well as to understand the current Brazilian scenario, which highlights the growing denial of secularism, based on moral and religious conservatism. For this, the pressures of religion on the school are analyzed, materialized in movements and bills, such as the Movement School Without Party, Homeschooling, Movement against “gender ideology”, and Religious Education itself. Based on the perspective of Historical-Critical Pedagogy (PHC), the importance of secularism and freedom of teaching is highlighted for a critical and human formation.